Legal challenges for the privacy and data protection of social networking sites (sns) in Malaysia: the case of facebook - Md Raus, Mohd Ikhsan; Md Tah, Ikmal Hisham; Yahya, Saadiah (University Teknology MARA Pahang, 2011)
The growth of the internet has made online social networking popular among billions of individuals around the world. However, these people seem to forget that somehow they are revealing their personal information to people who are not in the circle of friends. Exposing real names, uploading pictures, revealing private information and updating their current status are some of the features provided by the SNS. Furthermore, there is no awareness among the Malaysians who use Facebook especially about their rights and protections by the law. Despite the risks of using SNS, the Malaysian laws do not specifically address the legislation or rules to guide the usage of SNS but it has expanded towards several legislations that include Communication and Multimedia Act 1998, Computer Crimes Act 1997 and Data Protection Act 2010. This research focuses on legal issues in Malaysia such as personal data, cybercrime and the use of Facebook in the workplace.